A Negotiation-based control approach for disturbed industrial context. Issue 11 (2018) - Mezgebe, Tsegay Tesfay; Bril El Haouzi, Hind; Demesure, Guillaume; Thomas, Andre
Abstract: It is now accepted that using the multi-agents system (MAS) augments the reactivity to treat disturbances within flexible manufacturing system. Each agent could have different capability (evolution, learning, etc.) and the whole physical and control system, based on the agent interaction, could lead emerging behaviors to dynamically adapt a production schedule. Intelligent control algorithms shall be used to define these variables and all smart entities within their environment have to continuously negotiate for their final common goal. This paper proposes a negotiation-based reactive control approach to deal with the variability on manufacturing processes. A simulation experiment on the basis of full sized academic experimental platform was used to test how the negotiation-based reactive control approach could optimize priority based product sequencing. The product and resource agents have been built to negotiate considering different production performance measures. This has been done with expectations that the applicability of the negotiation-based reactive decision making process will be more adaptable to a production change than myopic decisions.